Risk Assessment of FCAW-GS Welding on TKY Joints in Offshore Wind Farm Jacket - Iwan Tri Prasetyo; Intan Baroroh; Buana Ma’ruf; Ali Azhar; Akhmad Basuki Widodo (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Offshore wind farms are vital in supporting the global energy transition, requiring high structural integrity, particularly in welded T-K-Y joints of jacket foundations. These joints must endure harsh marine environments and dynamic loads, making weld quality a critical factor. This research aims to identify, analyze, and mitigate the risks associated with Flux Cored Arc Welding – Gas Shielded (FCAW-GS) on T-K-Y joints in offshore wind farm jacket construction using the Failure Mode and Effect Analysis (FMEA) method. The study used expert surveys to assess risk factors based on Severity (S), Occurrence (O), and Detection (D), which were quantified into Risk Priority Numbers (RPN). A 5x5 risk matrix was employed for visualization, and mitigation strategies were developed based on the highest RPN values. The most significant risks identified were: inadequate preheating in T-joints (RPN 158.33), poor inter-pass cleanliness in K-joints (RPN 308.00), and similar cleanliness issues in Y-joints (RPN 264.44). After implementing risk mitigation measures such as welder training and strict inter-pass cleaning procedures, the weld rejection rate was reduced to only 1.2% out of 998 joints. The application of FMEA proved effective in prioritizing and controlling welding risks. This structured risk management approach—aligned with ISO 31000:2018—contributed to improved weld quality and reliability in offshore wind farm construction.